2017
DOI: 10.1298/ptr.e9911
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between changes of contralesional cortical activity and motor function recovery in patients with hemiparetic stroke

Abstract: ABSTRACT. Objective: To investigate the correlation between changes of contralesional cortical excitability evaluated by transcranial magnetic stimulation (TMS) and functional recovery in patients with hemiparetic stroke. Methods: Eight inpatients (mean age: 75.9 13.8 years) with mild to moderate hemiparesis were enrolled. TMS was delivered to the optimal scalp position over the contralesional (ipsilateral to the paresis) primary motor cortex (M1) to activate the unaffected flexor carpi radialis muscle (FCR) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The excitability of the contralesional motor cortex shows physiological plasticity during functional recovery after stroke, and hyperactivity in the contralesional motor cortex occurs early after stroke [ 8 ]. Decreased contralesional M1 activity is correlated with functional recovery [ 35 ]. Cortical activity is well reflected by the amplitude of the MEP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The excitability of the contralesional motor cortex shows physiological plasticity during functional recovery after stroke, and hyperactivity in the contralesional motor cortex occurs early after stroke [ 8 ]. Decreased contralesional M1 activity is correlated with functional recovery [ 35 ]. Cortical activity is well reflected by the amplitude of the MEP.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that the amplitude of the MEP in the contralesional hemisphere significantly decreased after both contralesional low-frequency and lesional high-frequency rTMS. Matsuura et al [ 35 ] reported that the reduction of contralesional M1 hyperactivity was related to the functional recovery after stroke. Veldema et al [ 36 ] demonstrated that the greater the increase of ipsilesional corticospinal excitability, the better hand motor recovery.…”
Section: Discussionmentioning
confidence: 99%